2004
DOI: 10.1002/eji.200324416
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal intraepithelial lymphocytes prevent pathogen‐driven inflammation and regulate the Smad/T‐bet pathway of lamina propria CD4+ T cells

Abstract: Intraepithelial lymphocytes (IEL) play a key role in gut homeostasis and are critical effector cells preventing the inflammatory intestinal lesions induced in mice following oral infection with Toxoplasma gondii. In this intestinal inflammatory model, CD4 + T lymphocytes from the lamina propria (LP) synergize with the infected enterocytes to secrete pro-inflammatory chemokines and cytokines. In this study, we assessed the mechanisms accounting for the ability of IEL to modulate the inflammatory activity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 32 publications
1
49
2
3
Order By: Relevance
“…Our studies focused on the CD4 ϩ T cells from the lamina propria because we showed in this study as well as previously (17,40,41), that these CD4 ϩ T cells infiltrated the lamina propria and produced copious amounts of IFN-␥ following oral infection. We observed a reduced frequency of IFN-␥-producing CD4 ϩ cells from the lamina propria in irradiated WT mice that were reconstituted with BM from TLR9 Ϫ/Ϫ mice (Fig.…”
Section: Tlr9 Expressed By the Cells From Both The Hemopoietic And Nomentioning
confidence: 59%
See 1 more Smart Citation
“…Our studies focused on the CD4 ϩ T cells from the lamina propria because we showed in this study as well as previously (17,40,41), that these CD4 ϩ T cells infiltrated the lamina propria and produced copious amounts of IFN-␥ following oral infection. We observed a reduced frequency of IFN-␥-producing CD4 ϩ cells from the lamina propria in irradiated WT mice that were reconstituted with BM from TLR9 Ϫ/Ϫ mice (Fig.…”
Section: Tlr9 Expressed By the Cells From Both The Hemopoietic And Nomentioning
confidence: 59%
“…CD4 T cells (CD45RB high , CD25 Ϫ ), isolated from the lamina propria, were identified as a major player in the inflammatory process (41). Following infection, CD4…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid DCs isolated from murine PPs produced high levels of IL-10 and induced naive T cells to differentiate into cells that produced much higher levels of IL-10 than T cells primed with any other DC subset (36). PP DC-mediated induction of IL-10-producing CD4 ϩ T cells (37,38), and expression of TGF-␤ in the lung and gastrointestinal mucosae, play a particularly important role in maintaining local tolerance and homeostasis (37,39,40). Similarly, oral delivery of exogenous recombinant SIgA and SIgA-based immune complexes contribute to orchestrate noninflammatory responses (this study) by triggering secretion of IL-10 and TGF-␤ by mucosal CD4 ϩ T cells (10).…”
Section: Discussionmentioning
confidence: 99%
“…cDNA was subjected to real-time PCR by using a ABI 7000 sequence detector (Applied Biosystems) (36 30 pmol of the ␣-subunit of the epithelial sodium channel (ENaC), and 35 pmol of the cystic fibrosis transmembrane conductance regulator (CFTR) primers. The primers used for MyD88, ␣-ENaC, and CFTR were the same as those previously described (33,37).…”
Section: Real-time and Rt-pcrmentioning
confidence: 99%